IMPLEMENTATION OF LEARNING MODELS PBL- REDIPPER FOR INCREASE ABILITY THINK CRITICAL AND COLLABORATION STUDENTS ON ATOMIC STRUCTURE MATERIAL - Pravita Saktiyani; Hari Sutrisno (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Study This aim For analyze influence application of learning models Problem-Based Learning integrated REDIPPER (PBL-REDIPPER) against ability think critical (KBK) and ability collaboration (KOL) participants educate on the material atomic structure . Type of research used is experiment quasi - experimental with​ design pretest-posttest control group design . Subject study involving 72 participants educate class XI in one of the senior high schools in Cirebon Regency which is divided into to in two groups , namely class experiments (n = 36) with the PBL-REDIPPER model and class control (n = 36) with the Direct Instruction (DI) model . Research data collected use instrument test essay ability think critical and sheet observation skills collaboration that has been validated . Data analysis techniques using analysis Multivariate Analysis of Variance (MANOVA) assisted by IBM SPSS Statistics 26. Analysis results statistics multivariate show that the PBL-REDIPPER model provides influence very significant simultaneity to ability think critical and collaborative participant educate in a way simultaneously (p = 0.007 < 0.01$) with contribution practical as big as 13.4% of which is included in category effect moderate . Univariate test results partial also confirms significant differences in each variable bound , where the learning model give contribution effect as big as 13.1% ( category currently ) to variation ability think critical (p = 0.002), and as big as 11.5% ( category currently ) to variation ability collaboration participant educated (p = 0.004). With Thus , the implementation PBL-REDIPPER syntax is proven effective in facilitate reconstruction draft abstract chemistry at a time optimize competence sociocognitive 21st century participants educate .